(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the importance of teaching profession and its tasks, the tasks and responsibilities of students in the woodworking workshop, the topic of "wood materials" by FSMU technology, "wood materials" in the table "SWOT-ANALYSIS", information about wood materials, i.e. wood hardness, compactness, grouping of wood according to the degree of hardness, the technology of making frames from wood materials, as well as the science of technology in everyday life are illuminated.